PEMBERDAYAAN MASYARAKAT DALAM PENINGKATAN BREASTFEEDING SELF-EFFICASY DI WILAYAH KERJA PUSKESMAS TUNAS HARAPAN - Indah Fitri Andini; Eva Susanti; Kurniyati Kurniyati (LPPM Universitas Al Muslim, 2023)
Breastfeeding Self Efficacy is a mother's belief to breastfeed her baby which influences effort, thought process and response when encountering difficulties in breastfeeding. The factors that influence a mother's self-efficacy are mastery experiences, other people's experiences, verbal persuasion, somatic and emotional conditions. The success of exclusive breastfeeding cannot be separated from the mother's factor, namely the desire and confidence of the mother to breastfeed. Mothers who have a high level of self-efficacy will breastfeed longer than mothers who have a low level of self-efficacy in breastfeeding. The solution offered by the implementing team was to increase the knowledge and skills of cadres through training on how to increase knowledge about breastfeeding self-efficacy for pregnant and breastfeeding women. The method for developing this activity was by providing training and refreshing for Posyandu cadres and village midwives as well as assisting cadres during the implementation of the activity. This activity achieved several results, namely the formation of ASI cadre groups through the WhatsApp media, and availability of facilities and infrastructure to support activities such as modules, tools and materials to increase the knowledge and skills of cadres on how to improve Breastfeeding Self Efficacy. After the training, there was an increase in the cadres' knowledge and skills about Breastfeeding Self-Efficacy.